A synergistic, global approach to revising the trypanorhynch tapeworm family Rhinoptericolidae (Trypanobatoida) - Herzog, Kaylee S.; Jensen, Kirsten (PeerJ, 2022)
Since 2010, the trypanorhynch tapeworm family Rhinoptericolidae Carvajal & Campbell, 1975 has housed just two distinctive, monotypic genera (Rhinoptericola Carvajal & Campbell, 1975 and Nataliella Palm, 2010). However, global collections of tapeworms from sharks and rays over the last more than three decades brought to light the need for major revision of the family by suggesting a much greater species-level diversity for the nominal genus Rhinoptericola. Through synonymy and the description of new species, the number of species in the genus is increased from one to eight. A phylogenetic analysis of the D1–D3 gene region of 28S rRNA (28S), including seven of the now nine species of rhinoptericolids, and a broad sampling of the other Trypanobatoida is the first to recover a monophyletic Rhinoptericolidae. In addition to systematic revision, this study allowed for the first evaluation of the degree of intraspecific vs interspecific variation in 28S for adult trypanorhynchs across the various hosts and geographic localities from which they have been reported, suggesting a relatively consistent boundary for Rhinoptericola. It is further suggested that detailed scanning electron microscopy (SEM) images of both the basal and metabasal armatures greatly aid in the interpretation of hook arrangement and shape. A schematic to streamline determination of the tentacular surface presented in scanning electron micrographs and line drawings of trypanorhynchs is presented for species with both two and four bothria. In combination, these methodological refinements can now be used as a model to resolve issues of classification and non-monophyly within both major lineages of the Trypanorhyncha. As a result of the taxonomic work, Rhinoptericola megacantha Carvajal & Campbell, 1975 (previously only known from the American cownose ray from the Chesapeake Bay and the Ticon cownose ray from the Gulf of Mexico, Venezuela, and Brazil) is now known from an additional species of cownose ray and a species of stingray, and is revealed to have a transatlantic distribution. Data from SEM suggest a simpler interpretation of hook arrangement in the metabasal armature for Rhinoptercola and—in combination with 28S sequence data—support Shirleyrhynchus Beveridge & Campbell, 1988 (a former rhinoptericolid) as its junior synonym. The three species formerly assigned to Shirleyrhynchus are thus transferred to Rhinoptericola. Data from light microscopy on whole-mounted specimens and histological sections, SEM, and 28S showed the eutetrarhynchid Prochristianella jensenae Schaeffner & Beveridge, 2012b to be morphologically consistent with species of Rhinoptericola and it is thus transferred to the genus. The type series of P. jensenae was determined to be mixed, representing two distinct species which are here redescribed and described as new, respectively. Two additional novel species of Rhinoptericola are described from cownose rays from off Mozambique and the Gulf of California.
Keywords: Rhinoptericola; Shirleyrhynchus; Scanning electron microscopy; 28S rRNA; Tentacular armature; Elasmobranchs; Synonymy; Prochristianella jensenae; Phylogeny; Species boundaries